Microbial communities and pharmaceutical contaminants in the water-soil–plant continuum of sugarcane crops irrigated with contaminated waters from the Cauca River Valley, Colombia - Juan Ceballos-Castillo; Rodrigo A. Echeverry-Gallego; Diana Martínez-Pachón; Alejandro Moncayo-Lasso; Javier Vanegas (Environmental Science and Pollution Research, 2026)
“Agricultural irrigation with contaminated water poses a major risk to food security and public health. This study examined contaminant transfer across the water–soil–plant continuum in sugarcane crops irrigated with water from the Cauca River, Colombia. Microbial community composition was characterized using 16S rRNA gene sequencing, while pharmaceutical active compounds (PhACs) in irrigation water and sugarcane plants were quantified by UHPLC–MS/MS. Microbial analyses revealed a potential biological pathway of microorganisms from water and soil into plant endophytic tissues. Bacterial diversity decreased markedly, from more than 400 genera identified in water and soil to only 64 genera detected within endophytic tissues. Nine potentially pathogenic genera-including Escherichia–Shigella , Pseudomonas , and Bacillus - were found across all matrices, suggesting microbial internalization. Bioinformatic predictions indicated the presence of genes associated with virulence traits (e.g., antimicrobial resistance and biofilm formation) as well as beneficial functions such as nitrogen fixation and phosphate solubilization. In parallel, high concentrations of PhACs were detected in irrigation water, including valsartan (up to 1309 ng L⁻ 1 ) and diclofenac (up to 969 ng L⁻ 1 ), whereas none or only low concentration detected in sugarcane tissues. Overall, the primary risk to human health appears to stem not from chemical uptake but from microbial infiltration shaped by environmental pressures. Therefore, managing plant-associated microbiomes is essential to mitigate health risks while harnessing biotechnological potential for sustainable agriculture.”